Computational study of elemental mercury control using g-C3N4-based adsorbents and catalysts - Liu, Shuai (2020)
The emission of elemental mercury (Hg0) from coal-fired power plants is very hazardous to environment and human beings, which make it of great necessary to take measures to significantly reduce the emission amount of Hg0. A great number of technologies have been developed to accomplish this goal and the methods behind these technologies are the adsorption and oxidation manners of Hg0 on the solid surfaces. A progressive review is made to know the primary information about sources, damages and laws of Hg0, the techniques used in industries, the mechanism employed in this technologies, and the sorbents, oxidants and catalysts developed. It is found that the legislation of Hg0 release is becoming more and more strict in recent years. The transformation technologies of Hg0 to Hg2+ and Hgp are the main process for Hg0 removal. In order to achieve effective capture of Hg0, the sorbents including carbon-based materials, metal and metal-oxides-based materials as well as the solid waste of fly ash were commonly used. For Hg0 oxidation, the halogen-related gases, O-containing gases and S-related gases are the main oxidants were usually introduced to oxidize the Hg0 from flue gas. The catalysts of noble metal, metal oxides are the main active components over the support for Hg0 oxidation. The recent development of structure, preparation, and application in Hg0 removal of carbon nitride (g-C3N4) were also provided. Since the g-C3N4 manifests excellent confinement effects of single atom and small clusters.. The action of embedding single transition metals and dimer configurations into g-C3N4 is feasible. Thus the investigation of Hg0 oxidation on these models were performed. In the case of Hg0 oxidation on Mn-g-C3N4 with O2, the Hg0, O2, and HgO adsorption behaviors were studied. O2 shows the highest affinity to the surface and is easily dissociated on the Mn-g-C3N4 slab. The Hg0 will be physisorbed above and reacts with one of O, forming OHgO structure, then HgO vapor will be generated. Two possible reaction paths are discussed based on the two adsorption configurations of dissociated two O atoms. It is concluded that Hg0 oxidation can take place on the surface in the presence of O2. As there are many transition metals listed in the periodic table, thus it is necessary to filter them to obtain better single atom for oxidizing Hg0. The reaction energy of the formation of OHgO structure is adopted to screen the possible metals, and the results shows that the VIIIB group metals (Fe, Co, Ni, Pd, Pt and Rh) are more favorable to conduct this oxidation process. Further analysis of Hg0 and O adsorption shows that O2 will be more strongly attached onto the single metals than Hg0, indicating a E-R mechanism of Hg oxidation. The relative energy profile of Hg oxidation tells that Ni is more suitable as the catalyst for Hg0 oxidation. The energy barriers have strong correlations with O adsorption energy. Dimer has two active atom compared with single atom, which would provide wider reaction place for Hg oxidation. Thus, Fe, Co and Ni-dimer@g-C3N4 are established to perform Hg oxidation process in the presence of O2. The results show that the energy barriers for the interaction of Hg0 with O is easier than that on single atom catalysts. And the HgO desorption is rate-determining step in the whole steps. Ni-dimer@g-C3N4 is identified the most potential catalyst. Interestingly, the active site of dimer will be changed to O-adsorbed dimer after first HgO molecule desorption. Besides, in the study of Hg0 adsorption, the model of Pdn(n=1-4)/g-C3N4 is built on which Hg0 shows high affinity to the pure single Pd atom and small clusters. With incorporation of them into g-C3N4 monolayer, the Hg0 interaction force to single Pd/g-C3N4 is lowered while the high interaction of Hg0 with cluster/g-C3N4 is retained and even extended. The Pd2/g-C3N4 shows leaset adsorption energy of Hg0. Moreover, the Pd4/g-C3N4 exhibits multi-active sites for Hg0 and highest capacity of Hg0 with high Hg0/Pd ration. In a word, Hg oxidation is feasible on single atom or dimer embodied g-C3N4 monolayer and single Ni and Ni-dimer are identified as the most effective catalysts to carry out the reaction. In addition, the Hg0 can be well removed by the sorbents of Pdn/g-C3N4 with high efficiency.